G99(P) Group Education in Adolescent Diabetes Transition. (4th June 2013) - Reid, H; Potts, L; Agostini, K; Luscombe, J; Thompson, R; Hindmarsh, P; Viner, RM; White, B
Abstract : Aims: Education is a key component of the transition process. We piloted a half-day group education session for young people (YP) and their parents. Methods: All YP in the diabetes service aged 14–19 years were invited via letter, email (if address available) and/or telephone. Eligible participants were invited to book using a commercial web-based booking platform. Education was in the form of expert-delivered didactic group sessions and a parent workshop. Members of the adult diabetes team introduced their service and were available to meet families. Attendees completed evaluation forms at the end of the session. Results: Demographics: 25/130 (19%) of eligible YP and 21 parents attended. 1/23 (4%) eligible YP aged 14 years attended, 8/50 (16%) aged 15–16 attended, 16/52 (28%) aged 17–18 years attended and 1/5 (20%) aged 19y attended. 17/25 (68%) YP in attendance were male. The mean (SD) HbA1c of attendees was 8.1% (1.4) vs 8.4% (1.7) for non-attendees (p, 0.05, t-test). 24/25 (96%) attendees had type 1 diabetes. Booking and attendance: Of those invited by email: 21/34 (62%) of YP opened the email, 30/39 (77%) of parents opened the email. The predominant barrier to attendance was exam commitments. Acceptability and ratings: Mean (SD) YP rating for the session was 8.1 (0.9) in a 10-point Likert scale (1 = very poor, 10 = excellent). Mean (SD) parent ratings were 8.6 (1.4). After the session, 14% of YP reported they were "ready to move to adult services", 59% "more ready to move to adult services", 18% "equally ready" and 0% "less ready". Sessions most frequently rated by YP as "useful" were "rights and jobs" (77%), "having a healthy baby" (64%), "driving and diabetes" (59%) and "alcohol and diabetes" (59%); parents most rated "driving and diabetes" (94%) "rights and jobs" (75%), "adult clinic" (75%) and "insulin pumps in adult services" (75%). Conclusions: An expert-delivered group transition education session shows promise as an effective and easy to deliver tool for preparing adolescent patients for adult life with diabetes. Further exploratory work is needed to optimise this model and measure its effectiveness.